2014
DOI: 10.1007/s00128-014-1367-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Danio rerio (Teleostei, Cyprinidae) During Two Stages of Development Based on Acute Toxicity Tests

Abstract: The sensitivity of Danio rerio to three chemicals was compared at two growth stages [larval (10 ± 2 after hatching) and post-larval (60 ± 4 days after hatching)] based on acute toxicity tests. Thirty-nine 48 h acute toxicity tests were performed with the substances CuSO4, NaCl and KCl. The 48 h LC50 values at the two growth stages were compared by independent samples t-tests. The results showed a clear decrease in sensitivity when post-larval organisms were used. Since acute toxicity test methods for D. rerio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Eggs were microscopically checked for fertility (overall fertility >90%) and viability. For the FET, embryos were used up to 90 min post fertilization, and for other comparative methods the organisms were nurtured until they had reached the appropriate age/size for testing following Freiry et al (). For all replicates, mortality rates of spawning events were <20% up to the latest life stage tested (juveniles).…”
Section: Methodsmentioning
confidence: 99%
“…Eggs were microscopically checked for fertility (overall fertility >90%) and viability. For the FET, embryos were used up to 90 min post fertilization, and for other comparative methods the organisms were nurtured until they had reached the appropriate age/size for testing following Freiry et al (). For all replicates, mortality rates of spawning events were <20% up to the latest life stage tested (juveniles).…”
Section: Methodsmentioning
confidence: 99%
“…The difference in toxicity between road salt and NaCl was attributed to the presence of other chemicals in road salt (such as cyanide) which might increase its toxicity to fish. Another study by Freiry et al, (2014) examined the differences in sensitivity of the zebrafish ( Danio rerio ) to three chemicals, including NaCl, at two stages of development. The results implied that the larval phase (10 days after hatching) of D .…”
Section: Impacts Of Deicers On Aquatic Resourcesmentioning
confidence: 99%
“…The results implied that the larval phase (10 days after hatching) of D . rerio is more sensitive (48‐h LC50 of 6.75 g/L) to NaCl than the post‐larval phase (60 days after hatching) with 48‐h LC50 of 8.9 g/L (Freiry et al, 2014). This study showed that the post‐larval stage of D .…”
Section: Impacts Of Deicers On Aquatic Resourcesmentioning
confidence: 99%
See 1 more Smart Citation